Effects of Fertilizer Levels on Growth and Yield Attributes of Three Dwarf Sweet Corn Varieties (Zea Mays L. Saccharata Strut) in Itu Flood Plain, Akwa Ibom State, Nigeria - A, Akpan, E.; S., Udoh, V. (Canadian Journal of Agriculture and Crops, 2017)
A study was conducted at the Cross River Basin flood plain located at Itu, during the early and late planting seasons of 2015 to assess the effects of fertilizer levels on growth and yield attributes of three dwarf corn varieties. Treatments consisted of four fertilizer levels (0, 200kg/ha, 300kgha and 400kg/ha) and three varieties of dwarf corn [Early sungrow hybrid (88544), Burpees triple crown AP white (88543), and Bi licious hybrid (89092)] and were laid in a randomized complete block design (RCBD) and replicated three times. Results showed significant different (≤0.05) in establishment percentage at early and late planting among the corn varieties but no significant effect on all other growth parameters studied. The 300kg/ha fertilizer rate produced tallest plants(15.17cm, 16.61cm and 43.45cm, 47.17cm) at 3 and 5WAP and highest number of leaves (4.69, 4.59) at 3WAP while 400kg/ha produced highest length of internode (2.73cm, 2.5cm and 6.79 cm, 7.14cm).The Cob length and number of seeds per Cob were significant in both seasons (p≤0.05%) with 400kg/ha fertilizer level producing highest number of seeds per Cob .Among the sweet corn varieties, white corn produced h longest cobs (18.00cm and 20.50cm), largest cob circumference (19.50cm and 18.58cm), and number of seed per cobs (306.60seeds and 410.00seeds) when treated with 400kg/ha NPK 15:15:15 fertilizer. The study revealed that 400kg/ha fertilizer level produced the highest grain yield compared with others in yield and some growth parameters, while 0 kg/ha competed fairly with 200kg/Ha, 300kg/Ha and 400kg/Ha.